Trajectory and Risk Factors of Persistent Decline in Health-Related Quality of Life after Septic Shock in Children with Preexisting Neurologic Disability - Prout, Andrew; Banks, Russell K.; Reeder, Ron W.; Zimmerman, Jerry J.; Meert, Kathleen L. (Journal of Pediatric Intensive Care, 2022)
Preexisting neurologic disability is common among children with septic shock. Life After Pediatric Sepsis Evaluation (LAPSE) was a multicenter cohort study that evaluated health-related quality of life (HRQL) in children with community-acquired septic shock. In this secondary analysis of LAPSE, we described the burden, trajectory, and risk factors for reduced HRQL in children with preexisting neurologic disability. Children (1 month–18 years) with community-acquired septic shock were evaluated for HRQL at baseline (reflecting prehospitalization status), day 7 and 28, and month 3, 6, and 12 following admission using the Pediatric Quality of Life Inventory or the Stein–Jessop Functional Status Scale. HRQL was expressed as a percentage of baseline scores. Of 365 evaluable children, 133 (36%) had preexisting neurologic disability. Neurologically disabled children had less decline in HRQL at day 7 (median −15% [interquartile range IQR: −38, 8] vs. −22% [−51, −3], p = 0.005) and day 28 (4% [−16, 22] vs. −11% [−37, 7], p < 0.001) than those without neurologic disability, and there was no difference in the extent of decline at month 3 (p = 0.241). Using multivariable modeling, higher baseline HRQL (odds ratio [OR] = 1.04 [95% confidence interval [CI]: 1.00, 1.08], p = 0.027) and acute renal dysfunction (OR = 1.08 [1.02, 1.16], p = 0.007) were associated with HRQL less than 90% of baseline at month 3 in neurologically disabled children who survived. Children with preexisting neurologic disability recover to baseline HRQL after septic shock sooner than those without neurologic disability. Higher baseline HRQL and acute renal dysfunction are risk factors for reduced HRQL in neurologically disabled children who survive sepsis.
Keywords: health-related quality of life; neurologic disability; sepsis; infant; child